2010
DOI: 10.1163/157181810x522360
|View full text |Cite
|
Sign up to set email alerts
|

The Ageing of the UN Convention on the Rights of the Child

Abstract: It is argued in this article that the U.N. Convention on the Rights of the Child (CRC) is no longer up to date. Compared with the new situation of children using the internet, cell phones, sending text messages, downloading videos, gaming and gambling on line, the CRC looks like an archaic document, the author found. Adolescents consume enormous amounts of alcohol and some have to be treated for addiction, but the term alcohol can't be found in the CRC. The CRC does not include the right to treatment for drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…An immediate finding revealed that while the digital creates opportunities for youth, it poses new challenges to the UN CRC, especially in view of the rapidly changing communication modes that are now part of children and young people’s everyday lives. It is in this regard, Veerman (2010) noted that the UN CRC has aged, and it needs updating in the face of new realities for children and youth: the presence and use of the Internet; cell phones; texting; mobile gaming; social networking sites such as Facebook, Twitter, YouTube, Instagram, Tumblr, Snapchat and WhatsApp; and the ever-increasing social networking apps that have resulted in new forms of risks and harm. While children’s exposure to violence, access to inappropriate content, privacy, cyberbullying, hate speech and so on – intrinsic to new media and the digital – are important, the question of how we take into account the socio-political dimensions that impede children’s rights caused by occupation, economic inequalities exacerbated by neoliberal globalization, privatization of public spaces, services and utilities in the Global South looms more important than ever.…”
Section: Resultsmentioning
confidence: 99%
“…An immediate finding revealed that while the digital creates opportunities for youth, it poses new challenges to the UN CRC, especially in view of the rapidly changing communication modes that are now part of children and young people’s everyday lives. It is in this regard, Veerman (2010) noted that the UN CRC has aged, and it needs updating in the face of new realities for children and youth: the presence and use of the Internet; cell phones; texting; mobile gaming; social networking sites such as Facebook, Twitter, YouTube, Instagram, Tumblr, Snapchat and WhatsApp; and the ever-increasing social networking apps that have resulted in new forms of risks and harm. While children’s exposure to violence, access to inappropriate content, privacy, cyberbullying, hate speech and so on – intrinsic to new media and the digital – are important, the question of how we take into account the socio-political dimensions that impede children’s rights caused by occupation, economic inequalities exacerbated by neoliberal globalization, privatization of public spaces, services and utilities in the Global South looms more important than ever.…”
Section: Resultsmentioning
confidence: 99%
“…CRC provisions need to be recognized as a compromise that was reached at a certain point in time through long negotiations; they are not absolute truths. Long-time advocates of child rights, such as Freeman (2000) and Veerman (2010), have pointed to the weaknesses of the Convention, especially in light of new societal developments. In a complementary manner, Poretti et al (2014) have revealed the political side of child rights protection; why and when certain topics appeal, and then disappear.…”
Section: Calls For Critical Analysismentioning
confidence: 99%
“…how to define children's best interests (Kelly, 1997) – and thus subject to considerable (adult) discretion. The UNCRC's coverage is arguably inadequate (e.g., child marriage is not explicitly addressed) and it may not be capable of addressing emerging issues, such as digital media (Veerman, 2010). Amendments have been made to the UNCRC and additional, optional protocols potentially extend the coverage of children's rights.…”
Section: Children's Rightsmentioning
confidence: 99%